Carrier Excitation Energies from a QD to OCL, RMS of Relative QD-Size Fluctuations and Temperature Dependence of QDL - R. M. Hassan (University of Thi-Qar Journal of Science, 2019)
In this work, we study the characteristic temperature of a quantum dot laser (QDL) inpresence of internal optical loss and quantum efficiency. The control parameters (the constantcomponent of internal loss coefficient, effective cross section, carrier excitation energies from a QD to the optical confinement layer (OCL), and the root mean square (RMS) of relativeQD-size fluctuations) are used for achieving free carrier density in the OCL and threshold current density and its component.